DEVELOPMENT OF A DISASTER MITIGATION BOOK FOR ELEMENTARY SCHOOL STUDENTS - Putri Mahanani; Listyo Yudha Irawan; Choirul Anam; Seli Septiana Pratiwi (Jurnal Cakrawala Pendas, 2024)
The background to the problems faced in society, especially the Malang area, East Java, is that several natural disasters have occurred which have resulted in victims. Therefore, education is needed from an early age in order to minimize the number of victims of natural disasters. The aim of this research is to develop a disaster mitigation book for disaster education in elementary schools. The development of learning media in the form of disaster mitigation books is very necessary so that elementary school students have readiness, both knowledge and skills related to the threat of disasters around them and can behave well when a disaster occurs. The research method used is development research with the ADDIE model. Activities are carried out in the stages of Analysis, Design, Development, Implementation and Evaluation. The data collection techniques used were questionnaires and documentation. The research subjects involved were material experts and media experts for elementary school education. Data analysis uses percentage techniques and descriptions of research results. The research procedure starts from initial analysis, product design, product development, product application, and product evaluation. The research results show that the book developed received a positive response from validators. Based on the assessment of material expert validators, the product obtained results of 93.75%. Based on the assessment of media experts, the book product received a score of 98%. These results prove that the product developed can be categorized as a very valid product based on the results of expert validator assessments and can be said to be suitable for elementary school students.